Firm age and the evolution of borrowing costs: Evidence from Japanese small firms - Sakai, Koji; Uesugi, Iichiro; Watanabe, Tsutomu (Journal of Banking & Finance, 2010)
This paper investigates how firms’ borrowing costs evolve as they age. Using a new panel data set of about 100,000 bank-dependent small firms for 1997–2002 and focusing on the channel of “adaptation” (i.e., surviving firms’ borrowing costs decline as they age) and that of “selection” (i.e., total borrowing costs decline as defaulting firms exit), we find that the reputation hypothesis suggested by Diamond (1989) provides a more plausible explanation of the downward sloping age profile of borrowing costs than the firm dynamics (Cooley and Quadrini, 2001) or the relationship banking (Boot and Thakor, 1994) hypothesis. In addition, we examine whether the firm selection process in Japan has been natural or unnatural. Our findings suggest that it has been natural in that firms with lower quality are separated, face higher borrowing costs, and are eventually forced to exit, which contrasts with the results of previous studies on credit allocations in Japan, including Peek and Rosengren (2005). Further, we find that the evolution of borrowing costs is partially due to selection but is mainly attributable to adaptation.